A cross-sectional study on smartphone uses among pregnant women attending childbirth classes in the Metropolitan Area of Palermo, Italy: The Stop-Phone study - Costantino, C.; Mazzucco, W.; Bonaccorso, N.; Sciortino, M.; Cimino, L.; Pizzo, S.; Conforto, A.; Calò, I.; Giliberti, D.; Gambino, C. R.; Segreto, D.; Maiorana, A.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Prevalence of mobile device addiction has increased over the years; both women and men have assimilated the mobile phone as a central component of their personal existence: integrating it into their lifestyle or becoming so dependent on it that life without it has become unimaginable. Smartphones generate radio-frequency electromagnetic fields. While short-term exposure in adults was considered quite safe, effects of long-term exposure or exposure during pregnancy on fetuses or during breastfeeding on newborns are not well studied yet. The objective of the present study was to investigate the prevalence and usage characteristics of smartphones among a sample of pregnant women, and promote the correct and conscious use of the smartphone.Methods. A cross-sectional study was conducted, with a questionnaire administered during childbirth classes and - after the questionnaire administration - an educational intervention focused on promoting the correct and conscious use of smartphones was carried out by psychologists and psychotherapists. Results. The findings of our study suggest that a significant number of the participants suffered addiction to mobile phone usage, but were not aware of it. More than two third of the sample (67.2%) have not changed their smartphone use habits since the beginning of their pregnancy and even more significant data shows that almost all future moms (98.3%) never speak with their doctor about smartphone use during pregnancy. Conclusions. Data collected suggest a lack of attention to the proposed topic, especially in relation to pregnancy. It seems necessary to sensitize future mothers on this topic. The promotion of a more conscious and controlled use of electronic devices can help reduce the radiation to which the unborn child may be exposed, but has a fundamental role even after birth, to ensure an adequate psychomotor and relational development of the child and do not affect, due to uncontrolled use of smartphones, the mother-child relationship.